The Impact of Folklore-Based Elaboration Learning on Elementary Students' Critical Literacy Skills - Ismail Ismail; Asbar Asbar; Syawal Sitonda; Elihami Elihami (Edumaspul: Jurnal Pendidikan, 2024)
This study aimed to assess the effectiveness of an elaboration-based storytelling approach in improving critical literacy skills among elementary students at SDN 13 Curio. The intervention involved storytelling sessions that used culturally relevant folklore, combined with elaborative questioning techniques to foster deeper understanding. The sample consisted of 30 students, with pretest and post-test measures used to evaluate changes in literacy skills, supported by qualitative observations of student engagement.The findings revealed a significant improvement in post-test scores compared to pretest results, indicating the success of the storytelling-based intervention. A paired sample t-test confirmed that the observed gains were statistically significant (t = 9.45, p < 0.001). Additionally, a strong positive correlation (r = 0.840, p < 0.01) was found between participation levels and literacy skill improvement, emphasizing the importance of active engagement in the learning process. Qualitative observations also showed high levels of participation, with students responding enthusiastically to culturally relevant materials.In conclusion, the elaboration-based storytelling model effectively enhanced critical literacy by fostering engagement and a deeper understanding of narrative content. This approach contributes valuable insights into educational methods for developing critical thinking skills in elementary students. Future research should explore the long-term impact of this intervention and its applicability across diverse educational settings to establish broader generalizability and sustainability.